Training For Improving Students Mathematics Ability by Using SOWISO Application - Rosi Widia Asiani; Cut Multahadah; Susi Marisa; Hairini Hairini (Fakultas MIPA Universitas Negeri Padang, 2022)
The learning situation after the COVID-19 pandemic has not fully recovered. Mathematics learning, especially at the tertiary level, is carried out using a blended learning model, namely some learning is carried out face-to-face and partly online. Therefore, adequate learning media or applications are needed so that learning can take place optimally. One of the media that can be used as a solution to this problem is the Sowiso application. The sowiso application is a media in the form of a digital book that is equipped with exercises so that it is possible to improve students' mathematical concept understanding skills. Therefore, a training was held with the theme